The Role of Environmental Accounting on Waste Management - Abdul Kharis Almasyhari; Wulan Suci Rachmadani; Yeni Priatnasari (Shirkah: Journal of Economics and Business, 2024)
Drawing on the role of environmental accounting in waste management as a social responsibility, the present research aims to assess the agency's awareness and implementation of environmental accounting in its waste management practices. Using a descriptive qualitative approach, data were gathered through in-depth interviews with four environmental agency staffs and observations of financial reports. The findings reveal significant gaps in understanding and applying environmental accounting principles, with a lack of integration into financial management practices. Despite an emerging awareness of its importance, the agency’s current practices do not fully align with sustainable financial management, particularly regarding environmental conservation and cost accountability. The study suggests that targeted educational initiatives and systematic integration of environmental accounting are essential to improving both environmental stewardship and financial sustainability within the agency. The implications of these findings highlight the need for structural changes in how environmental considerations are accounted for in public sector financial systems, potentially serving as a model for other municipalities aiming to enhance their environmental responsibility.